2010
DOI: 10.1162/jocn.2009.21386
|View full text |Cite
|
Sign up to set email alerts
|

Neural Dissociations between Action Verb Understanding and Motor Imagery

Abstract: Abstract■ According to embodied theories of language, people understand a verb like throw, at least in part, by mentally simulating throwing. This implicit simulation is often assumed to be similar or identical to motor imagery. Here we used fMRI to test whether implicit simulations of actions during language understanding involve the same cortical motor regions as explicit motor imagery. Healthy participants were presented with verbs related to hand actions (e.g., to throw) and nonmanual actions (e.g., to kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(161 citation statements)
references
References 66 publications
11
143
3
Order By: Relevance
“…Although these results indicate that overlapping activation reported previously for AE and word comprehension (e.g., Rueschemeyer et al, 2007;Hauk et al, 2004) probably does not reflect a common neural substrate, shared activation reported in conjunction with AO and word comprehension indeed result from common neural resources (e.g., Aziz-Zadeh et al, 2006). Interestingly, a previous study has shown that action word comprehension activates neural resources distinct from those engaged by instructed motor imagery (Willems, Toni, Hagoort, & Casasanto, 2009); thus, the internal observation of actions suggested here contrasts with imagining what it would be like to perform an action oneself and is more comparable with the process of visually perceiving another acting.…”
Section: Lateral Pmccontrasting
confidence: 50%
“…Although these results indicate that overlapping activation reported previously for AE and word comprehension (e.g., Rueschemeyer et al, 2007;Hauk et al, 2004) probably does not reflect a common neural substrate, shared activation reported in conjunction with AO and word comprehension indeed result from common neural resources (e.g., Aziz-Zadeh et al, 2006). Interestingly, a previous study has shown that action word comprehension activates neural resources distinct from those engaged by instructed motor imagery (Willems, Toni, Hagoort, & Casasanto, 2009); thus, the internal observation of actions suggested here contrasts with imagining what it would be like to perform an action oneself and is more comparable with the process of visually perceiving another acting.…”
Section: Lateral Pmccontrasting
confidence: 50%
“…These results suggest that the distinctive motor features of verb meanings may be coded in the precentral motor cortices in ways that reflect individual differences in how the designated types of actions tend to be performed (for additional data consistent with this view see Beilock et al, 2008;Lyons et al, 2010). Further research is needed, however, to elucidate exactly how the neural coding of the motor features of verb meanings relates to the neural coding of not only the execution, but also the observation and imagination, of the matching kinds of actions within the frontal lobes (for steps in this direction see Willems et al, 2010b;MoodyTriantis et al, 2014;Rueschemeyer et al, 2014).…”
Section: Activation Patternsmentioning
confidence: 99%
“…To create these ROIs, we selected the peaks of activation reported by Rüschemeyer et al (2007) for the interaction between Complexity and Motor-Relatedness in the left postcentral gyrus and the left parietal operculum (S2). However, since the postcentral gyrus peak reported by Rüschemeyer et al (2007) is slightly more posterior than what is usually reported for motor words (Hauk et al, 2004;Postle et al, 2008;Willems, Toni, Hagoort, & Casasanto, 2009), we also created a more anterior ROI. As our study was a partial replication of Rüschemeyer et al's study, we also based this ROI on peaks of activation reported by the former study, but this time for the Simple Motor versus Non-Motor contrast.…”
Section: Roi Analysesmentioning
confidence: 99%